Eksekusi Barang Rampasan Hasil Tindak Pidana Kehutanan Pasca Putusan Mahkamah Konstitusi Nomor 021/PUU-III/2005 - Rifai, Eddy; Triyono, Rakhmat (Jurnal Konstitusi, 2015)
This study examines the execution of the judgment against the spoils of crime Â in forestry. Research using normative juridical approach and empirical jurisdiction. Execution of judgments against the state spoils of criminal offenses in the field of forestry, the injunction decision declared goods confiscated for the state not to do execution the form of an auction, because of legislation prohibiting the sale of forest products obtained from crime in protected forests. Perspective execution of court decisions to loot the proceeds of crime in the field of forestry is to judge using breakthrough progressive law, the court ruled that the injunction which reads "Evidence confiscated to the state and used for social purposes".